2013
DOI: 10.1016/j.bbamem.2013.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin disrupts lipid bilayers in a polyQ-length dependent manner

Abstract: Huntington's Disease (HD) is a neurodegenerative disorder that is defined by the accumulation of nanoscale aggregates comprised of the huntingtin (htt) protein. Aggregation is directly caused by an expanded polyglutamine (polyQ) domain in htt, leading to a diverse population of aggregate species, such as oligomers, fibrils, and annular aggregates. Furthermore, the length of this polyQ domain is directly related to onset and severity of disease. The first 17 N-terminal amino acids of htt have been shown to furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
105
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(117 citation statements)
references
References 66 publications
12
105
0
Order By: Relevance
“…167, 212, 248 Both normal and mutant htt localizes to numerous subcellular compartments, i.e. endosomes, pre-synaptic, and clathrin-coated vesicles, and dendritic plasma membrane.…”
Section: Interaction With Lipids Influence Polyq Aggregation and Locamentioning
confidence: 99%
See 2 more Smart Citations
“…167, 212, 248 Both normal and mutant htt localizes to numerous subcellular compartments, i.e. endosomes, pre-synaptic, and clathrin-coated vesicles, and dendritic plasma membrane.…”
Section: Interaction With Lipids Influence Polyq Aggregation and Locamentioning
confidence: 99%
“…With the localization of htt to membranous surfaces well established, it is appropriate to note that lipids are a common modulator of amyloid formation, as studies of α-synuclein, 254, 255 islet amyloid polypeptide, 256 β-amyloid, 257259 and polyQ 179, 212, 260, 261 all demonstrate altered aggregation in the presence of membranes when compared to bulk solution. With regards to the amyloid formation in general, several physicochemical properties of lipid membrane, i.e.…”
Section: Interaction With Lipids Influence Polyq Aggregation and Locamentioning
confidence: 99%
See 1 more Smart Citation
“…However, rat IAPP (rIAPP), which does not readily form fibrils (19), has also been seen to cause membrane leakage in vitro (16) and confer some (albeit strongly reduced) cytotoxicity in vivo (12). Also, the nonamyloidogenic hIAPP (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) fragment as well as a number of nonamyloidogenic full-length variants of IAPP have been observed to cause leakage of synthetic membranes (13,15,20), and hIAPP (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and rIAPP (1)(2)(3)(4)(5)…”
mentioning
confidence: 99%
“…Legleiter et al have used in situ AFM to directly monitor the interaction between huntingtin (htt) exon 1 protein and brain lipid extract [158]. They observed that the exon1 fragments accumulated on the lipid membranes comprised of total brain lipid extract, which caused disruption of the membrane.…”
Section: Lipidmentioning
confidence: 99%